TRADISI PA’JUKUKANG PERSPEKTIF AL ‘URF - Maabi, Husnul; Abdul Halim Talli; Andi Muhammad Akmal (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
The main problem discussed in this research is the Pa'jukukang Tradition in Pa'jukukang District, Bantaeng Regency, al' Urf Perspective. The type of research used is qualitative research with a theological, sociological and syar'i approach. The data collection method is carried out through observation, interviews and documentation, so that it can describe and analyze phenomena, attitudes, beliefs and assessments of society individually and in groups. The research results show that the phenomenon of the Pa'jukukang tradition in Bantaeng Regency still exists among the community, becoming a culture that continues to be preserved and celebrated every year. However, looking at their daily habits, it turns out that there is deviant behavior related to this tradition, both in terms of intention and in terms of implementation. As in the belief that you will receive blessings/favor if you bring various types of food when you want to hold a celebration. If seen from al 'urf's point of view, of course deviant behavior is not justified because it contains elements that can damage a person's faith. The implication of this research is that it is important for the government and local religious leaders to collaborate and take firm steps in order to provide direction and guidance to all elements of society which will hopefully be able to reduce little by little activities that can lead to polytheism. Then turn it into an ordinary activity or tourist spot like tourist attractions in general.